Single and Binary Adsorption Systems of Rhodamine B and Methylene Blue onto Alkali-Activated Vietnamese Diatomite - Pham Dinh Du; Huynh Thanh Danh (Adsorption Science & Technology)
Diatomite was slightly modified with a sodium hydroxide solution. The resulting material was characterized by using energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and nitrogen adsorption-desorption isotherms. The so-treated diatomite has a high specific surface area (77.8 m2/g) and a high concentration of isolated silanol groups on the surface, and therefore, its adsorption capacity increases drastically in both the single and binary adsorption systems for rhodamine B and methylene blue. The binary system is more effective than the single system, with methylene blue being adsorbed more than rhodamine B. The adsorption process is spontaneous and fits well with the Langmuir isothermal model, and it depends on pH significantly.